PROS AND NEGATIVES OF TRANSFERRING AGRICULTURAL LAND TO OTHER LAND CATEGORIES - Turayev Ruhiddin Amirkulovich; Safayev Sanjarbek Zafarbek oglu (Web of Journals Publishing, 2026)
The article analyzes the positive and negative aspects of the process of transferring agricultural land to other land categories (land conversion) on a scientific and theoretical basis. The importance of land conversion from the perspective of efficient use of land resources, economic development, environmental sustainability, and social consequences is revealed. Also, scientific conclusions are given on the problems associated with changing the land category in the conditions of Uzbekistan and their mitigation.
Keywords: Land conversion, land management, agricultural land, land resources, sustainable development, ecology, economics, land cadastre.